VALIDITAS DAN RELIABILITAS TERHADAP INSTRUMEN KEPUASAN KERJA - Rokhmad Slamet; Sri Wahyuningsih (Aliansi : Jurnal Manajemen dan Bisnis, 2022)
Research instruments with appropriate and consistent measuring instruments in research can be carried out with validity and reliability tests. Validity test can be done using Corrected Item to Total Correlation method and reliability test using Cronbach's Alpha method. The test uses a two-sided test with a significance level of 0.05 or 5%.Data retrieval using Google Forms with a trial of 50 respondents in the form of ordinal data with SPSS tools analyzed by variability test using Corrected Item to Total Correlation method and reliability test using Cronbach's Alpha method.As many as 4 instrument numbers out of 50 instrument numbers were declared invalid, namely numbers 7, 9, 12 and number 14, while the other instrument item numbers were declared valid. In the reliability test using Cronbach's Alpha method with Cronbach's Alpha value of 0.987 0.60 then all the instrument questions are declared reliable.